The Licious Cake Sdn Bhd / Chyindilinda Omiting ...[et al.] - Omiting, Chyindilinda; Jawahir Johari, Madrah; Nayuh, Nellyn Alicea; Engkok, Marlina; Ramli, Nurhidayah (2013)
The Licious Cake Sdn. Bhd. is a start-up bakery retail establishment located in 1 Borneo, Kota Kinabalu. We choose this location because what we have survey, this mall is a place that we can found our entire expected customer that is tourist student, family, and officers. This is because this mall is always busy or visited by these customers because its location is near with university area, office area, housing area such as Kingfisher, University apartment, etc and the most important it is also listed as one of attractive place for tourist. Overall, this company is run a business base on cake. We are producing ten types of cupcakes, six types of cake, and five types of cake in jar in a day. Customer that comes to our shop can have two choices either want to take away or enjoy our cake in our cafe. In advance, we also provide drinks in four choices; Hot Chocolate, Hot Chocolate Classic, Vanilla Cream Frappuccino Blended, and Green Tea Cream Frappuccino Blended. Furthermore, we also in ordering service for any party, wedding ceremony, official ceremony, etc. Where, we also provide delivering service for the ordering with terms and conditions. This company is equally owned and managed by its five partners. Miss. Chyindilinda Omiting is the general manager, Miss. Nadrah Jawahir Johan is the administration manager, Miss. Nellyn Nayuh is the operational manager, Miss. Marlina binti Engkok is the operational manager and the financial manager is Miss. Nurhidayah binti Ramli. Each of these members has RM 10,000 contributions in the capital to set up this business. We also hired two kitchen assistants and one driver to do the deliver job. Our mission is wants to be a cakes trendsetter and to provide remarkable services in delivering satisfaction and a value for money dining experience. The Licious Cake expects to catch the interest of a regular loyal customer base with its variety of cake products. We aim to offer our products at a competitive price to meet the demand of the middle-to higher-income local market area residents and tourists.